FRI0182 Pharmacokinetics and immunogenicity of mavrilimumab administered subcutaneously in subjects with rheumatoid arthritis. (23rd January 2014) - Wu, C.-Y.; Chen, X.; Lu, H.; Esfandiari, E.; Magrini, F.; Godwood, A.; Ryan, P.; Kane, C.; Roskos, L.; Wang, B.
Abstract : Background: Mavrilimumab is a high-affinity, fully human immunoglobulin G (IgG) monoclonal antibody that selectively binds to the α subunit of GM-CSF receptor (GM-CSFRα). A Phase 2a randomized, double-blind, placebo-controlled, multiple ascending dose study was conducted to evaluate the efficacy, safety, pharmacokinetics (PK) and immunogenicity of mavrilimumab in subjects with at least moderately active rheumatoid arthritis (RA). Objectives: To characterize the PK and immunogenicity of mavrilimumab after multiple subcutaneous administrations to RA patients (10-100 mg Q2W x7). Methods: Serum samples for mavrilimumab concentration determination and the detection of the presence of anti-drug antibodies (ADA) were collected from all RA subjects at pre-designated timepoints, and analyzed using validated electrochemiluminescence assay (PK) or enzyme-linked immunosorbent assay (ADA). Noncompartmental PK data analysis was performed using WinNonlin (Pharsight Corp, St Louis, MO). Exposure-response relationship was assessed using a population modeling approach. Results: Maximum serum mavrilimumab concentrations (Cmax) were observed approximately 3 days following SC administrations. The PK exposure (Cmax and AUC) of mavrilimumab increased more than dose-proportionally across the investigated dose range (10-100 mg). Mavrilimumab was cleared more rapidly at lower dose levels due to the GM-CSF receptor-mediated clearance. The average PK half-life was approximately 13 days at 100 mg dose level when GM-CSFRα was fully occupied by mavrilimumab. Three (3.8%) placebo subjects and 20 (13%) mavrilimumab-treated subjects had positive ADA during the study period. The relationship between PK and RA disease activity was adequately described by a direct Emax model. Conclusions: The observed mavrilimumab PK profiles in this Phase 2a study were consistent with prior projections from a mechanistic population model 1 . The PK parameters of mavrilimumab following SC dosing are typical of a monoclonal antibody with target-mediated disposition. The PK and immunogenicity properties of mavrilimumab, and the direct exposure-response relationship support further clinical development of mavrilimumab for the treatment of RA. References: Wang, B. et. al., Mechanistic Modeling of Antigen Sink Effect for Mavrilimumab Following Intravenous Administration in Patients With Rheumatoid Arthritis. Journal of Clinical Pharmacology (in press), 2012 Disclosure of Interest: C.-Y. Wu Employee of: Medimmune, X. Chen Employee of: Medimmune, H. Lu Employee of: Medimmune, E. Esfandiari Employee of: Medimmune, F. Magrini Employee of: Medimmune, A. Godwood Employee of: Medimmune, P. Ryan Employee of: Medimmune, C. Kane Employee of: Medimmune, L. Roskos Employee of: Medimmune, B. Wang Employee of: Medimmune